Dinarippiger gen. nov. (Tettigoniidae: Bradyporinae: Ephippigerini), a new saddle bush-cricket genus for Ephippiger discoidalis Fieber, 1853 from the Dinaric karst - Skejo, Josip; Kasalo, Niko; Fontana, Paolo; Ivković, Slobodan; Tvrtković, Nikola; Rebrina, Fran; Adžić, Karmela; Buzzetti, Filippo Maria; Ćato, Sebastian; Deranja, Maks; Gomboc, Stanislav; Scherini, Roberto; et al. (Zootaxa, 2023)
A new genus of the tribe Ephippigerini, Dinarippiger Skejo, Kasalo, Fontana et Tvrtković gen. nov., is described based on the characters of occiput coloration, tegmina coloration, cerci and pronotum shape. The new genus is morphologically intermediate between the genera Ephippiger Berthold, 1827 and Uromenus Bolívar, 1878, and presently includes only Dalmatian Saddle Bush Cricket, Dinarippiger discoidalis (Fieber, 1853) comb. nov., hitherto known as Ephippiger discoidalis Fieber, 1853. The species inhabits NE Italy (mainly Carso Triestino), SW Slovenia, Croatia, Bosnia & Herzegovina, and Montenegro, i.e., islands and karst habitats along the eastern Adriatic coast, with isolated findings in Albania and Italy. Its prominent variation in size and coloration has already produced many synonyms (= limbata Fischer, 1853, = limbata var. major Krauss, 1879, = limbata var. minor Krauss, 1879, = selenophora Fieber, 1853, = sphacophila Krauss, 1879), which may suggest that what is currently regarded as a single species could represent a complex of distinct species with restricted distributions. This study also presents an annotated distribution map and a bioacoustic analysis of D. discoidalis comb. nov. Further research, especially adopting molecular methods, is necessary to assess possible cryptic diversity within the genus Dinarippiger gen. nov. and elucidate its evolutionary history.